Primary Clear Cell Adenocarcinoma of the Cervix: A Clinical Analysis of 18 Cases without Exposure to Diethylstilbestrol - Dongying Wang; Chunhua Zhao; Li Fu; Yang Liu; Weiyang Zhang; Tianmin Xu (Hindawi Limited, 2019)
Objectives. Cervical clear cell adenocarcinoma (CCAC) is a rare malignant tumor with independent biological behavior in the female reproductive system. In this report, we collect the clinical and histopathological characteristics of 18 CCAC patients without exposure to diethylstilbestrol (DES) and conduct relevant clinical analysis. Methods. We retrospectively analyzed the clinical data of 18 patients with CCAC who were diagnosed and treated from January 2009 to August 2017 in the Second Hospital of Jilin University. Results. A total of 18 patients were enrolled. The age of patients ranged from 37 to 74 years with the peak incidence between 45 and 55 years. The median age was 53 years. The most common symptom was vaginal bleeding (66.7%, 12/18). The most common type of lesion was the endocervical type (66.7%, 12/18). The negative rate of human papillomavirus (HPV) examination was 88.9% (8/9). Based on the staging criteria of the International Federation of Gynecology and Obstetrics (FIGO) cervical cancer clinical stage in 2018, 55.6% patients were stage I (n=10), 16.7% were stage II (n=3), 22.2% were stage III (n=4), and 5.6% were stage IV (n=1). Seventeen patients underwent surgery; 64.7% (11/17) of cases showed infiltration of the entire layer of the cervix, pelvic lymph node (PLN) metastasis was observed in 4 patients (26.7%, 4/15), endometrium metastasis was observed in 4 patients (25%, 4/16), and 13 patients (72.2%, 13/18) were diagnosed at an early stage (stage IB1-IIA2). Fifteen patients' immunohistochemistry indicated that napsin A, CK7, CK (AE1/AE3), and PAX-8 were positive, and p53, p16, ER, and vimentin were expressed to different degrees. Follow-up data were obtained in 13 patients (72.2%, 13/18). One patient died of recurrence 5 months after surgery, and the other patients' progression-free survival (PFS) ranged from 9 to 59 months. Tumor size (>4 cm), tumor stage (FIGO IIA2-IV), PLN, and endometrium metastasis had negative effects on PFS (P<0.05). Conclusions. CCAC is a highly invasive malignant tumor, whose pathogenesis may not be associated with HPV infection. Radical hysterectomy combined with chemotherapy (paclitaxel + platinum) has the ideal short-term curative effect. In the future, larger samples of clinical data are required to confirm these insights.